2010
DOI: 10.1063/1.3475314
|View full text |Cite
|
Sign up to set email alerts
|

Unabsorbed Seyfert 2 galaxies: the case of “naked” AGN

Abstract: Hawkins (2004) reported on a class of "naked" AGN characterized by strong amplitude optical brightness variability and the complete absence of broad emission lines in the optical spectrum. The variability suggests that the nucleus is seen directly, however the absence of broad lines contradicts the simple formulation of Unified Models for AGN. We present the results of quasi-simultaneous spectroscopic observations with XMM-Newton and NTT (La Silla) of two "naked" AGN. We confirm the "naked" nature of Q 2131-42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Spectral analyses have shown that the optical type vs. X-ray properties for most AGN generally agree with the predictions from AGN unification models. However, in recent years, the number of cases where the predictions from AGN unification models do not match the observations has increased substantially, as significant absorption has been detected in ∼10% type-1 AGN (Cappi et al 2006;Mateos et al 2005b;Akylas et al 2004) while type-2 AGN have been detected without any signatures of X-ray absorption (Panessa et al 2009;Bianchi et al 2008;Corral et al 2005;Panessa & Bassani 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Spectral analyses have shown that the optical type vs. X-ray properties for most AGN generally agree with the predictions from AGN unification models. However, in recent years, the number of cases where the predictions from AGN unification models do not match the observations has increased substantially, as significant absorption has been detected in ∼10% type-1 AGN (Cappi et al 2006;Mateos et al 2005b;Akylas et al 2004) while type-2 AGN have been detected without any signatures of X-ray absorption (Panessa et al 2009;Bianchi et al 2008;Corral et al 2005;Panessa & Bassani 2002).…”
Section: Introductionmentioning
confidence: 99%